Issues Associated With Covid-19 and Its Consequences on University Education in Nigeria - Olugbenga Timothy Ajadi; Adeola Oyebisi Egbedokun (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study explored the various issues associated with covid-19 as well as the consequences of the pandemic focusing on university education in Nigeria. Methodology: Using a literature review methodology, this study uses a qualitative descriptive-analytical technique. Secondary sources include scholarly publications, journal articles, and historical assessments, while primary sources include Sharma and Veer's work on the actions and issues surrounding the Covid19 outbreak and Sanz et al.'s study on the effects of the coronavirus crisis on schooling. Main Findings: According to the study, the pandemic has caused unprecedented changes in the manner that university education is delivered in Nigeria overall, and as Nigerian universities lack a contingency plan, they must switch to an electronic form of instruction. In particular, the study discovered that the pandemic had negatively impacted student welfare and caused a discernible rise in both unintended pregnancies and school dropout rates. Novelty/Originality of this study: Nigerian institutions lack face-to-face interaction in all its forms, and students' lives are rearranged against their desire to socialize with their classmates on campus during the pandemic. Introduction of a new standard learning platform that uses technology to replace the university's current traditional learning mode.